The Tectonics of the Double Skin:: Green Building or Just more Hi-Tech Hi-Jinx? - Meyer Boake, Terri; Harrison, Kate; Collins, David; Balbaa, Taymoore; Chatham, Andrew; Lee, Richard; Bohren, Andre (ARCC Conference Repository, 2019)
Double skin façade systems are employed increasingly in high profile buildings, designed by famous Architects, using acclaimed engineering consultants, and being touted as an exemplary "green” building strategy. It is a new technology that is more often found in high-end European and Pacific Rim architecture, and far less often in North American building. For the majority of mainstream architects, double skin technology remains elusive. From perspectives of both knowledge and budget, double skin systems are often beyond the scope of most commercially driven, North American projects. The question arises as to whether or not double skin buildings truly are more environmentally responsible and sustainable. Is North American commercial architecture missing out on potential energy and environmental savings? The Double Skin Façade is based on the notion of exterior walls that respond dynamically to varying ambient conditions, and that can incorporate a range of integrated sun-shading, natural ventilation, and thermal insulation devices or strategies. Early modern architects such as Le Corbusier, with his "mur-neutralisant”7, and Alvar Aalto, in the window design of the Paimio Sanitorium, explored this new building technology. Early solar passive design exemplified in the "trombe” wall, is also viewed as a precursor to modern double skin systems.8 Only recently has double skin technology become analogous with explorations in transparent and glass architecture, and moreover, acclaimed as environmentally "responsible” design. This paper represents the findings of a team of upper level B.Arch. and Masters students who have conducted an initial investigation into double skin cladding systems. The study has allowed us to begin to ascertain whether or not these systems represent a valid approach to energy efficient and environmentally responsible design or are, as they might appear, just another "cool” high-tech style. Does this type of skin system represent environmentally "responsible' versus "responsive” design? The end result of the research will be posted on the School website so that it can be shared with others interested in the findings.9